2016
DOI: 10.1080/10503307.2016.1189619
|View full text |Cite
|
Sign up to set email alerts
|

This is what I need a clinical feedback system to do for me: A qualitative inquiry into therapists’ and patients’ perspectives

Abstract: In what should increase our confidence toward core aspects of ROM, we suggest that an integration of relational feedback concepts and stringent clinical dimension tracking into the ROM/CFS can be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 37 publications
4
65
0
Order By: Relevance
“…Inconsistency can be caused by plausible heterogeneity on how therapists actually use ROM systems, by differences on the type of measures included in the system, or by the algorithms and formats of feedback it provides, the type of therapy, among many other factors. Research is needed that unveils how feedback is used and the mechanisms by which feedback influences outcomes (Amble et al., ; Janse et al., ; Moltu et al., ). Greenhalgh, Long, and Flynn () hypothesized that the lack of consistent impact of outcome feedback into practice may be due to the nomothetic nature of the assessment tools used, which provide too general information, whereas therapeutic processes are individualized.…”
mentioning
confidence: 99%
“…Inconsistency can be caused by plausible heterogeneity on how therapists actually use ROM systems, by differences on the type of measures included in the system, or by the algorithms and formats of feedback it provides, the type of therapy, among many other factors. Research is needed that unveils how feedback is used and the mechanisms by which feedback influences outcomes (Amble et al., ; Janse et al., ; Moltu et al., ). Greenhalgh, Long, and Flynn () hypothesized that the lack of consistent impact of outcome feedback into practice may be due to the nomothetic nature of the assessment tools used, which provide too general information, whereas therapeutic processes are individualized.…”
mentioning
confidence: 99%
“…It seems that this type of information is important to patients and facilitates discussions concerning worries that may not be brought up by patients otherwise . Furthermore, a qualitative trial on patients in psychiatric treatment found that open conversation and collaboration were considered important features in a clinical feedback system for patients and therapists alike .…”
Section: Discussionmentioning
confidence: 99%
“…PM measures are most likely to improve care when clinicians review results promptly and use findings to guide clinical practice (de Jong, van Sluis, Nugter, Heiser, & Spinhoven, ). Further, prior qualitative research evidence suggests that clinicians are more likely to use PM measures that are easy to use and interpret, pose minimal time burden, and measure constructs that they view as essential to patient progress (Bickman et al, ; Moltu et al, ). To optimize implementation and dissemination, a PM measure must not only be valid for assessment of ED symptoms in intensive treatment but must also be viewed as acceptable and useful for informing treatment among stakeholders.…”
Section: Introductionmentioning
confidence: 99%